Research on the impact of the project team on selected areas of project management - Artur Biskupek (Trends Economics and Management, 2019)
Purpose of the article: The following article consists of two parts. The basis of the first one is a literature study in the field of project team management. The paper presents cumulative information about the project team. Among other things, it provides the basic information, such as the definition of a project team, the composition of the project team and the most popular structures of the project team's operation in the implemented projects. The second part of the article presents the results of the research carried out on a sample of 73 respondents (who sent back a correctly completed questionnaire) in terms of the impact of the project team on the success of the implemented project. The survey consists of 23 questions. The first three were cafeteria questions, the next two were about the meaning of the project team and the rest was about the survey topic. The analysis was made using descriptive statistics and the whole article is concluded with a summary. Methodology/methods: The only criterion for taking part in the study was project management. The research tool was a questionnaire sent to the respondents by e-mail, following the earlier information contact carried out by telephone or e-mail. The entire research process began with pilot studies. The whole process was divided into three stages. Scientific aim: The aim of the study was to analyse the impact of the project team on the project's course. Findings: The conclusion that can be drawn after the study is that the project team is one of the most relevant success factors in the whole project management process. Conclusions: The obtained results of the research in the process of analysis and interpretation allow stating that the project team has a significant impact on the entire project. The project team is characterised by such a large impact on the course of the entire undertaking that it can be successfully called the decisive. This means that it can decide about the success or failure of the entire project.
Keywords: M15; M19; 650; project management; project team; project team management; research; survey